Smart contracts and a dual blockchain structure for collaborative tourism - Zohra Temmar; Asmaa Boughrara (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This article optimizes a decentralized system for collaborative tourism in Alge ria using blockchain, smart contracts, and proof of reputation (PoR) consensus. The system matches services into organized trips, manages reservations, and automates payments to ensure transparency and autonomy without centralized authority. This work opens the door to exploring dual-blockchain architectures. Building on a previous work, we enhanced node interactions, automated con tract execution, and introduced a dual-blockchain structure to reduce latency while improving scalability and security.